Pattern and trend of deliberate self harm at emergency department of Patan hospital, PAHS - Shrestha, Sitaram (Journal of General Practice and Emergency Medicine of Nepal, 2014)
Introduction: Deliberate self-harm is a major problem in the developing world. This study aims at observing the general pattern and sociodemographic variables related to it. Methods: Present study is a hospital based Prospective study which included all age group of patients with DSH. During study period ie from April 2010-to march 2011 AD, one hundred and six patients were seen in emergency department with history of deliberate self harm (DSH). Results: Study showed more female patients than male. Common age for DSH falls on fifteen to twenty five. House wife and students were mostly involved in DSH. Patients mostly used organ phosphorus compounds for DSH. Majority of patients discharged or admitted in medical ward, but six patients died despite of management in emergency department. Conclusion: DSH is a problem in our community which need to be studied more extensively.